Measurement of CP violation in B0 → D*±D∓ decays - Aaij, Roel; Archilli, Flavio; Bachmann, Sebastian; Berninghoff, Daniel; Borsato, Martino; Braun, Svende; Comerma-Montells, Albert; D'Argent, Philippe; Dembiski, H.-P.; Dziewiecki, Michal; Gerick, David; Grabowski, Jascha; et al. (Journal of high energy physics, 2020)
The decay-time-dependent CP asymmetry in B0→ D∗±D∓ decays is mea- sured using a data set corresponding to an integrated luminosity of 9 fb−1 recorded by the LHCb detector in proton-proton collisions at centre-of-mass energies of 7, 8 and 13 TeV.